2018
DOI: 10.1175/bams-d-17-0197.1
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Boundary Circulation and Hydrography Off Angola: Building Angolan Oceanographic Capacities

Abstract: The eastern boundary region off Angola encompasses a highly productive ecosystem important for the food security of the coastal population. The fish-stock distribution, however, undergoes large variability on intraseasonal, interannual, and longer time scales. These fluctuations are partly associated with large-scale warm anomalies that are often forced remotely from the equatorial Atlantic and propagate southward, reaching the Benguela upwelling off Namibia. Such warm events, named Benguela Niños, occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 59 publications
1
76
0
Order By: Relevance
“…The observed opposing flow regimes in the two central water layers compare well with the results obtained by Peña‐Izquierdo et al () who suggested by analyzing hydrographic data and the output of an assimilation model opposing circulation cells in the upper and lCW layers. Equatorward flow below the poleward eastern boundary currents was also observed in the upwelling region off Peru (e.g., Chaigneau et al, ) and off Angola (Tchipalanga et al, ), suggesting that it is a common feature of EBC. Our data show stronger equatorward flow during the relaxation season compared to the upwelling season in that depth range, pointing to a baroclinic response of the circulation to the wind stress curl as a driving mechanism.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The observed opposing flow regimes in the two central water layers compare well with the results obtained by Peña‐Izquierdo et al () who suggested by analyzing hydrographic data and the output of an assimilation model opposing circulation cells in the upper and lCW layers. Equatorward flow below the poleward eastern boundary currents was also observed in the upwelling region off Peru (e.g., Chaigneau et al, ) and off Angola (Tchipalanga et al, ), suggesting that it is a common feature of EBC. Our data show stronger equatorward flow during the relaxation season compared to the upwelling season in that depth range, pointing to a baroclinic response of the circulation to the wind stress curl as a driving mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…A significant influence of equatorially forced CTWs on the seasonality of the Mauritanian EBC as found, for example, for the Angolan (Kopte et al, ; Tchipalanga et al, ) EBC has not been reported. Polo et al () showed that signals of intraseasonal coastal Kelvin waves forced at the equator to extend to latitudes less than 15°N, only.…”
Section: Introductionmentioning
confidence: 92%
“…Continuous measurements were carried out during several along-and cross-shelf sections off Angola and Namibia ( Figure 1). The ATZ is a transition band between the equatorial Atlantic and the BUS and it is characterized by seasonal cooling and shoaling of the thermocline (maximum in austral winter) in association with coastally trapped waves (Hutchings et al, 2009;Tchipalanga et al, 2018). The ATZ is a transition band between the equatorial Atlantic and the BUS and it is characterized by seasonal cooling and shoaling of the thermocline (maximum in austral winter) in association with coastally trapped waves (Hutchings et al, 2009;Tchipalanga et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…Since our survey exceeded the northern boundary of the BUS (∼16 • S; Lutjeharms & Meeuvis, 1987), and for comparison, we divided our study area in three domains: Angola Tropical Zone (ATZ; 10-14 • S), Angola-Benguela Front (ABF; 14-16 • S), and nBUS (16-28.5 • S). The ATZ is a transition band between the equatorial Atlantic and the BUS and it is characterized by seasonal cooling and shoaling of the thermocline (maximum in austral winter) in association with coastally trapped waves (Hutchings et al, 2009;Tchipalanga et al, 2018). The ABF is a thermal front that separates warm, oligotrophic tropical waters of the Angola Current (AC) from cold waters upwelled further south (Mohrholz et al, 2001(Mohrholz et al, , 2008.…”
Section: Study Areamentioning
confidence: 99%
“…Likewise, the existence of the data and the observing efforts are not visible through JCOMMOPS and hence are not recognized as a contribution to the GOOS. Tchipalanga et al (2018) provide an example of a typical "bottle neck" case in the FOO context: they found that further time series research on physical data from RV Nansen cruises revealed new insight into fish stock dynamics, creating the potential for prediction and thus better management. In the FOO ocean observing value chain framework, the Tchipalanga et al (2018) example demonstrates that by bringing the third FOO Pillar "Data Management and Information Products" from Pilot readiness levels 5 (verification) to readiness level 6 (demonstration of availability, use, interoperability), a different class of ocean observing product is made available in the Angolan EBS.…”
Section: Ocean Observing In Ebs Regions From a Fisheries Viewmentioning
confidence: 99%